HUBUNGAN ANTARA BI RATE DAN INFLASI PERIODE JULI 2005 – DESEMBER 2011 : UJI KAUSALITAS TODA – YAMAMOTO - Banu Yodiatmaja (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
BI Rate and inflation have a graphic phenomenon that is almost moving in the same direction, but the direction and relationship are still uncertain. The phenomenon of real inflation in majority which is not reached in accordance with the inflation target in the period of policy framework of Inflation Targeting Framework (ITF) makes the relationship between these two macroeconomic variables become more questionable remember the importance of effectiveness and efficiency of monetary policy which is implemented. Therefore, this study aims to analyze whether there is a causal relationship between BI Rate and inflation in the implementation period of ITF working framework. The data analysis method used in this study was Toda-Yamamoto Causality Test along with the prerequisite tests; the stationarity test and lag length criteria test.Based on the results of data stationarity test conducted, the BI Rate and inflation variables were at the first difference. Meanwhile, the lag length criteria test resulted that lag 2 was the optimal lag selected to perform Toda-Yamamoto Causality Test. The results showed that the BI rate caused the changes of inflation rate in the two-month period indicated by Wald test p-value of 0.0000 in which the value was smaller than the confidence level of 1%, 5% and 10%. Vice versa, the inflation caused the change of BI Rate level at the same period of time indicated by Wald test p-value of 0.0001 in which the value was smaller than the confidence level used. In line with the results of study, it can be concluded that BI Rate is an instrument that can be used to control inflation to be maintained in accordance with the inflation target. Furthermore, when inflation has been in a low and stable level, BI Rate can be set at a low level in order to increase economic activities in the real sector.